Prenatal Testosterone Increases Sensitivity to Prenatal Stressors in Males with Disruptive Behavior Disorders - Martel, Michelle M. (Neurotoxicol Teratol, 2014)
Disruptive Behavior Disorders (DBD) exhibit a sex-biased prevalence rate favoring boys, and prenatal testosterone exposure appears to be part of the complex etiology of these disorders. The current study examines whether high prenatal testosterone exposure may heighten risk for DBD symptoms in males by increasing susceptibility to negative environmental conditions such as maternal nicotine and alcohol use during pregnancy. Participants were 109 three- to six-year-olds (64% male; 72% with DBD) and their 109 primary caregivers and 55 daycare providers/teachers who completed a multi-informant diagnostic procedure. A proxy of prenatal testosterone exposure, finger-length ratios, interacted with maternal report of prenatal nicotine use to predict teacher-rated hyperactivity-impulsivity during preschool, for boys, but not girls, although the three-way interaction was not significant. Prenatal testosterone interacted with prenatal alcohol exposure to predict teacher-rated hyperactivity-impulsivity and ODD symptoms differentially based on child sex (significant three-way interaction). Boys with higher levels of prenatal testosterone who were also exposed to higher levels of nicotine and alcohol during pregnancy exhibited increased hyperactivity-impulsivity during early childhood, but girls did not exhibit this same pattern. Thus, high prenatal testosterone exposure seems to increase risk for DBD symptoms particularly in males by increasing susceptibility to prenatal environmental stressors.